Factors Impacting People Performance Expectancy and Behavioral Intention with the Internet Medical Service in Chengdu, China - Yang, Yixi; Porntrakoon, Paitoon; Li, Jian (Local Administration Journal, 2024)
This research examined patients’ receptiveness to utilizing online medical services, explore the factors impacting their performance expectancy and behavioral intention, and offer actionable recommendations to enhance patient adoption and utilization of online medical services. The study was based on the unified theory of acceptance and use of technology and also drew upon the health belief model and social cognitive theory to elucidate the components. The cross-sectional survey included the participation of a total of 494 valid outpatients from the first affiliated hospital founded by the Chengdu Medical College of China through the use of convenience sampling and purposive or judgmental sampling. With Cronbach’s alpha and composite reliability greater than 0.7 and the average variance extracted greater than 0.5, all of the constructs demonstrated a satisfactory level of reliability and validity. Each and every one of the research hypotheses was validated. Both social influence and facilitation conditions were shown to have a considerable impact on performance expectancy, as evidenced by the statistically significant β values of 0.436 and 0.344 (p<0.001), respectively. Behavioral intention was substantially affected by resistance to change, effort expectancy, perceived security, performance expectancy, and perceived disease threat, as indicated by the β values of -0.196, 0.367, 0.308, 0.223, and 0.307, respectively, with p-values less than 0.001. Effort expectancy significantly predicted the behavioral intention to promote the adoption of Internet medical services. Therefore, the promotion of Internet medical services should focus on individuals who are well educated and have basic IT skills. Regular training sessions should be provided to broaden the intended user group.